2022
DOI: 10.3390/su14148350
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multiobjective Automatic Parameter-Calibration Framework for Urban Drainage Systems

Abstract: Urban drainage systems (UDSs) continue to face challenges, despite numerous efforts to improve their sustainability through design, planning, and management. The goal of such initiatives is to avoid and minimize flooding as well as maintain the UDS’s sustainable functionality, which can be analyzed using a stormwater management model (SWMM). In this study, a multiobjective automatic parameter-calibration (MAPC) framework was developed based on the SWMM. It consisted of three steps: sensitivity analysis (Step I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This approach significantly reduces the human influence and time consumption associated with manual calibration, thereby enhancing modelling efficiency and credibility. Kim et al established a coupled SWMM underground drainage network multi-objective automatic parameter calibration model for Seoul [14] using a Non-dominated Sorting Harmony Search (NSHS) algorithm. Experimental testing revealed that the calibrated model framework could effectively reflect system characteristics and address issues in pipe design, planning, and management, thereby contributing to simulation research.…”
Section: Introductionmentioning
confidence: 99%
“…This approach significantly reduces the human influence and time consumption associated with manual calibration, thereby enhancing modelling efficiency and credibility. Kim et al established a coupled SWMM underground drainage network multi-objective automatic parameter calibration model for Seoul [14] using a Non-dominated Sorting Harmony Search (NSHS) algorithm. Experimental testing revealed that the calibrated model framework could effectively reflect system characteristics and address issues in pipe design, planning, and management, thereby contributing to simulation research.…”
Section: Introductionmentioning
confidence: 99%
“…The interception and infiltration capacities of shrub were found to be greater than those of lawn, and the rainfall intensity and pattern were the major factors that influenced the interception and infiltration of rainwater (Xu et al, 2019). A multiobjective automatic parameter-calibration (MAPC) framework was developed based on the SWMM (Kim et al, 2022). LID modeling is still relatively new, and the understanding of model sensitivity to certain parameters is lacking (Panos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a structurally intricate distributed hydrological model, SWMM contains parameters that lack precise physical definitions in the process of model abstraction and simulation. These parameters, such as the impermeable manning coefficient, the depression storage in impermeable areas, and the minimum infiltration rate, are typically determined based on past experiences and may vary with different environmental factors [7][8][9][10]. Consequently, parameter calibration and validation are typically conducted during the urban stormwater runoff simulation process, to ensure the precision and applicability of the simulation results [11].…”
Section: Introductionmentioning
confidence: 99%